Vaccinia Virus Protein B18R: Influence on mRNA Immunogenicity and Translation upon Non-Viral Delivery in Different Ocular Cell Types - An-Katrien Minnaert; Joke Devoldere; Karen Peynshaert; Laure Vercruysse; Stefaan C. De Smedt; Katrien Remaut (MDPI AG, 2021)
In the last few years, interest has grown in the use of nucleic acids as an ocular therapy for retinal genetic diseases. Recently, our research group has demonstrated that mRNA delivery could result in effective protein expression in ocular cells following subretinal injection. Yet, although mRNA therapy comes with many advantages, its immunogenicity resulting in hampered mRNA translation delays development to the clinic. Therefore, several research groups investigate possible strategies to reduce this innate immunity. In this study, we focus on B18R, an immune inhibitor to suppress the mRNA-induced innate immune responses in two ocular cell types. We made use of retinal pigment epithelial (RPE) cells and Müller cells both as immortalized cell lines and primary bovine cells. When cells were co-incubated with both B18R and mRNA-MessengerMAX lipoplexes we observed an increase in transfection efficiency accompanied by a decrease in interferon-β production, except for the Müller cells. Moreover, uptake efficiency and cell viability were not hampered. Taken together, we showed that the effect of B18R is cell type-dependent but remains a possible strategy to improve mRNA translation in RPE cells.